PENGUATAN USAHA BUDIDAYA IKAN DENGAN PRODUKSI PAKAN BUATAN SECARA MANDIRI - Dian Bhagawati; Siti Rukayah; Agus Nuryanto; Sukirno Sukirno (Universitas Jenderal Soedirman, 2019)
Abstract Tilapia fish farmers in Kober Village, West Purwokerto Subdistrict have been able to produce single-sex male seeds due to a training that has been conducted by a team from the Biology Faculty of Unsoed. However another problem arose after the success is the increasing need for feed, so they must provide enough costs for feed. Eventually the target audience feels very burdened and wants to make their own feed by utilizing locally available materials. At the request of the young fish famer group, locally called as pokdakan, training has been made in the manufacture of artificial feed made from local raw materials. The aim is to develop appropriate technology that fulfill the needs of the community through training to educate the group members of pokdakan in Kober Village in planning, preparing feed composition, preparing tools and ingredients, mixing feed ingredients, striking and drying feed. The method applied was participatory, with stages of activities in the form of preparation, implementation of training, mentoring, and evaluation. The training activities were run smoothly and obtained a positive response from the target audience. The training participants have been able to produce pellets for fish feed with local raw materials, such as water hyacinth flour and tofu dregs. The pellets have no solid texture and can dry completely by sun-dried for two days, starting at 10:00 to 17:00. The success of making the pellet has increased the confidence of the members of the pokdakan, so as to be able to transmit knowledge that has been obtained to farmers in other villages. In addition, by being able to produce artificial feed independently, it can strengthen the cultivation of tilapia fish occupied so far, and reduce the cost of purchasing feed.